Psychological Outcomes of the COVID-19 Pandemic on People with Type 1 Diabetes Globally: A Scoping Review - Maizel, Jennifer L.; Dixon, Brittney N.; Walker, Ashby F. (Current Diabetes Reviews, 2023)
Background: People with type 1 diabetes (T1D) face heightened risks for morbidity and mortality from the 2019 Coronavirus (COVID-19). They also have elevated risks for disparate psychological outcomes during the COVID-19 pandemic, given their predisposition to mental health disorders, including anxiety and depression, and skyrocketing rates of these conditions among the general population. Methods: To investigate the psychological ramifications of the COVID-19 pandemic on people with T1D globally, we conducted a scoping review of recent literature across eight online databases. Articles were screened via a rigorous process, and data pertaining to psychological outcomes were coded into thematic areas for analysis. Results: Forty articles presenting data from 27 countries and 14 categories of psychological outcomes affecting people with T1D were included in this review. Psychological outcomes, in order of most to least frequently identified, included: stress, anxiety, social factors, worry, distress, fear, sleep habits, quality of life, depression, attitudes regarding COVID-19, other psychological issues, mental health services utilization, burnout, and temperament. Recurring findings demonstrated significant increases in the prevalence of mental health conditions, changes in sleeping habits, reductions of social support, and extensive psychosocial concerns among people with T1D. Associations between patients’ psychological issues and demographic characteristics, diabetes self-management behaviors, glycemic control, and overall wellbeing were evident. Conclusion: During the COVID-19 pandemic, people with T1D experienced pervasive psychological burdens. This review calls for further research examining the long-term impacts of the pandemic and strengthens awareness of the need for interventions to offset psychological challenges affecting people with T1D.
Keywords: coronavirus